ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN SYARIAH SEKTOR AGRIKULTUR PADA BANK UMUM SYARIAH (BUS) PERIODE 2015-2020 - Alvin Yahya; Andre Armanto (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Agricultural sector in Indonesia gives many contribution to the economy such as giving huge contribution towards PDB, becoming source of income for public, and being food producer for life necessities. However, agricultural sector still has some obstacles such as access to capital difficulties which are caused by majority has small business scale and banking perception that agricultural sector is as High Risk Industry. So that it is a need of support in Agricultural Sector, one of the available solutions is by syariah financing offered by Bank Umum Syariah. This study used quantitative study where the researcher would test the factors that influences the Agricultural Financing in Bank Umum Syariah (BUS). The sampling in this research was Non-Probability Sampling by using saturated sampling. The data used was quarterly secondary data from 2015 until 2020 which were obtained from Otoritas Jasa Keuangan website and Badan Pusat Statistik as the data resource analised by using Vector Autoregression (VAR) analysis tool with the help of E-Views 10 software. The result of the study showed that from the four independent variables there was only Produk Domestik Bruto variable which had a positive effect towards Agrucultural Financing. Whereas the Farmer’s Term of Trade Indices (NTP), Inflation and Non Performing Financing (NPF) had no effect on Agricultural Financing.